2008
DOI: 10.1146/annurev.micro.61.080706.093422
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase Elongation Factors

Abstract: The elongation phase of transcription by RNA polymerase is highly regulated and modulated. Both general and operon-specific elongation factors determine the local rate and extent of transcription to coordinate the appearance of transcript with its use as a messenger or functional ribonucleoprotein or regulatory element, as well as to provide operon-specific gene regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
136
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 159 publications
(226 reference statements)
0
136
0
Order By: Relevance
“…NusA is a 55-kDa conserved bacterial protein comprised of an N-terminal domain; the three domains S1, KH1, and KH2 with RNA-binding motifs; and two C-terminal acidic repeat domains AR1 and AR2 (5,6,24,44,48,49,57). In the present study, we identified a recessive substitution mutation in nusA that confers relief of transcriptional polarity (much like missense mutations in rho or nusG) but has no apparent effect on transcription elongation or antitermination in vivo.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…NusA is a 55-kDa conserved bacterial protein comprised of an N-terminal domain; the three domains S1, KH1, and KH2 with RNA-binding motifs; and two C-terminal acidic repeat domains AR1 and AR2 (5,6,24,44,48,49,57). In the present study, we identified a recessive substitution mutation in nusA that confers relief of transcriptional polarity (much like missense mutations in rho or nusG) but has no apparent effect on transcription elongation or antitermination in vivo.…”
mentioning
confidence: 71%
“…NusA in E. coli has been best studied as a transcription elongation factor and as a protein required for transcription antitermination in rrn operons and lambdoid phages (6,17,40,44,48). Previous reports have also suggested that NusA can indirectly affect Rho-dependent termination by its influence on the rate of transcription elongation and thereby on transcription-translation coupling (31,58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antitermination activity of N and Q, but not gp39, is enhanced by cell-encoded proteins, including transcription elongation factor NusA, which by itself stimulates termination but reverses its activity to additionally stabilize the TEC in cooperation with N and Q (5, 6). Curiously, the N, Q, gp39, and NusA proteins all target the flexible β flap domain of RNAP (2,4,(7)(8)(9)(10)(11) that forms a part of the RNA exit channel and has been implicated in intrinsic termination and transcription pausing through direct interaction with RNA hairpins (Fig. 1) (3,(12)(13)(14).…”
mentioning
confidence: 99%